Socio-cultural aspects of global economic processes - Pankova, Iuliia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
The paper considers existing theoretical approaches to the analysis of socio-cultural aspects of globalization economic processes. The relevance of the study is the fact that the process of globalization, which manifest sit self in various spheres of public life, since the second half of the twentieth century, provides both new opportunities and new challenges for humanity not only in the economy and geopolitics, but also in demography, ecology, technology, culture. Today, it is clear that the spread of the influence of globalization on the value-normative foundations of national cultures in different regions of the world often leads to problems of cultural identification. The subject of research of the article is the socio-cultural aspects of global economic processes. The goal is to study the evolution of the theoretical approaches to the analysis of the socio-cultural aspects of globalization economic processes and their impact on the overall civilization development. The objective is to research the issue of existing theoretical approaches to the analysis of socio-cultural aspects of globalization economic processes. General scientific methods are used, such as system analysis. The following results were obtained: today it is obvious that the spread of the influence of globalization on the value-normative bases of national cultures in different regions of the world often leads to problems of cultural identification. Conclusions: on the basis of the conducted research, it was concluded that globalization, which is understood as the aspiration of humanity to a single global space while preserving the diversity of peoples and cultures, cannot be effectively realized without changing the general paradigm of human development towards creating a harmonious system of universal value sand socio-cultural practices national cultures.